2022
DOI: 10.1136/bmjopen-2021-059305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychosocial and economic factors on the quality of life of patients with end-stage renal disease and their caregivers in Klang Valley, Malaysia: protocol for a mixed-methods study

Abstract: IntroductionThe number of patients in Malaysia requiring dialysis is expected to rise substantially in the future due to the ageing population and increasing prevalence of diabetes mellitus and hypertension. Hence, more individuals will be expected to adopt the role of caregivers in the future. The upward trend of end-stage renal disease (ESRD) and caregiving for dialysis patients has detrimental consequences for both patients and caregivers in terms of their psychological well-being and quality of life. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…When a family member becomes ill, the whole family has an emotional concern. The study by Ibrahim N et al showed a high correlation between the psychological well-being of caregivers and patients [ 14 ]. Gerogianni et al study stated that caregivers have higher levels of anxiety and depression when dialysis patients under their care have high levels of anxiety and depression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…When a family member becomes ill, the whole family has an emotional concern. The study by Ibrahim N et al showed a high correlation between the psychological well-being of caregivers and patients [ 14 ]. Gerogianni et al study stated that caregivers have higher levels of anxiety and depression when dialysis patients under their care have high levels of anxiety and depression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%